L'argumentation dans le contexte de l'entretien clinique: Revisiter Piaget et son actualité - Arcidiacono, Francesco; Perret-Clermont, Anne-Nelly (My University, 2009)
When Piaget visited Binet’s laboratory in Paris, and learned about the newly devised “intelligence tests”, he was soon very critical of the approach. In his opinion the child’s reasoning could not be assessed just by taking note of the child’s answers to preset questions. In order to better understand the functioning of the growing mind, Piaget developed a method that he called “clinical interview” or “critical interview” and used it in all his studies on the development of concrete and formal operations. Piaget claimed that with such an approach he could better investigate how children were reasoning because he would require from them, through appropriate conversations to give arguments to back up their answers.
In our on-going research, we are currently revisiting these “clinical interviews” and the piagetian claim that children are arguing according to their cognitive level, with the hypothesis that the children’s understanding of what they are supposed to think and talk about is highly dependent on their interpretation of the social setting in which they are asked to have a conversation, and this deeply affects their possibility to argue and to learn to argue. From the observations of these classical conversations, we hope to develop insights for a revisitation of Piaget’s fundamental suggestion that argumentation plays a central role both in the adult’s understanding of the child and in the child’s understanding of the world.
Keywords: adult-child interaction; conservation; argumentation; piagetian interview